Suspended Sentence in the Macedonian and Slovenian Criminal Law - Jovašević, Dragan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
In contemporary criminal law, a prison sentence is the basic and most important type of criminal sanction to be imposed on perpetrators of criminal acts in order to prevent and combat crime. But, next to an unconditional prison sentence, all criminal legislation also knows the different modalities of its imposition or execution. These are different forms of substitute or alternative in cases where unconditional detention is not necessary. Thus, we can distinguish full or partial suspension of the prison sentence or some other kind of punishment. In the first case, it is about the suspended sentence. This is a complete exemption from the execution of a court decision that handed down prison sentences or determined (and/or other types and extent of punishment) for a specified time (checking) and under certain conditions. In the case of a conditionally convicted person who does not meet the set of general and special, mandatory or optional requirements, criminal law provides for mandatory or optional revocation of the suspended sentence. However, in addition to the suspended sentence as a form or modality of execution of imposed prison sentences, some modern criminal laws recognise the suspended sentence as a special kind of criminal penalty – as a measure of warning. A prerequisite for the implementation of these measures is the fulfilment of the formal requirements – in terms of type and prison sentence duration, or material conditions – assessment of the court that the application of penalties in case of concrete, is not necessary because the goals (purpose) of punishment can be achieved without effective enforcement of prison sentences in whole or in part. This paper examines the concept, characteristics, conditions, and methods of implementation of these forms of prison sentence suspension in Macedonian and Slovenian criminal law.